PENEGAKAN HUKUM BALAP LIAR MOTOR ANAK DI WILAYAH POLDA METRO JAYA - Agung Prasetyo, Dimas; Gultom, Potler (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Illegal street racing is a social issue. Street racing is a race conducted outside official circuits, on public roads or other open areas not designated for racing. Street racing often involves various types of vehicles, including cars, motorcycles, and bicycles. This activity is frequently unregulated by law or lacks official permits, and is deemed highly dangerous for participants and the general public due to non-compliance with applicable rules. Sanctions can be imposed. The juridical-normative research employs primary and secondary data. The discussion results in law enforcement efforts both through preventive and repressive measures. According to Law Number 22 Year 2009, punitive measures include a fine of Rp. 3,000,000.00 under Article 309, and, to serve as a deterrent effect, the police can impound vehicles for two months. A managerial challenge faced by the Police is the passive or indifferent attitude of some members of the public towards illegal motorcycle racing actions.